Complementary effects of extracellular nucleotides and platelet-derived extracts on angiogenesis of vasa vasorum endothelial cells in vitro and subcutaneous Matrigel plugs in vivo - Roedersheimer, Mark (BioMed Central, 2011)
BACKGROUND: Platelets contribute to vascular homeostasis and angiogenesis through the release of multiple growth factors, cytokines and nucleotides, such as ATP and ADP. Recent reports have demonstrated a marked growth-promoting effect of total platelet extracts and selected platelet growth factors on therapeutic angiogenesis. However, since endogenous adenine nucleotides are rapidly degraded during the platelet isolation and storage, we examined whether supplementing a platelet-derived extract with exogenous adenine nucleotides would augment their pro-angiogenic effects. METHODS: Pulmonary artery vasa vasorum endothelial cells (VVEC) were used to examine the effects of dialyzed platelet-derived soluble extracts and extracellular adenine nucleotides on proliferation, migration and tube formation. In addition, an in vivo Matrigel plug assay was used to examine the effects of platelet extracts and adenine nucleotides on neovascularization of plugs subcutaneously placed in 50 ICR mice. The number of vascular structures in Matrigel plugs were evaluated by histological and statistical methods. RESULTS: Platelet extracts (6.4-64 μg/ml) significantly induced DNA synthesis and at a concentration of 64 μg/ml had a biphasic effect on VVEC proliferation (an increase at 48 hrs followed by a decrease at 60 hrs). Stimulation of VVEC with platelet extracts also significantly (up to several-fold) increased cell migration and tube formation on Matrigel. Stimulation of VVEC with extracellular ATP (100 μM) dramatically (up to ten-fold) increased migration and tube formation on Matrigel; however, no significant effects on cell proliferation were observed. We also found that ATP moderately diminished platelet extract-induced VVEC proliferation (48 hrs) and migration, but potentiated tube formation. Neither ATP, or a mixture of non-hydrolyzable nucleotides (ATPγS, ADPβS, MeSATP, MeSADP) induced vascularization of Matrigel plugs subcutaneously injected in mice, however, the combination of these nucleotides with platelet extracts dramatically increased the number of functional capillaries in the Matrigel plugs. CONCLUSION: Data from this study suggest that platelet-derived growth factors and extracellular nucleotides represent important regulatory signals for angiogenesis. Supplementation of platelet extracts with exogenous adenine nucleotides may reveal new possibilities for therapeutic angiogenesis and tissue regeneration approaches.